The reduction of methane production in the in vitro ruminal fermentation of different substrates is linked with the chemical composition of the essential oil - García, Florencia (2020)
Fil: García, Florencia. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias. Córdoba, Argentina.